2022
DOI: 10.1186/s12889-022-13866-7
|View full text |Cite
|
Sign up to set email alerts
|

“The pandemic made us stop and think about who we are and what we want:” Using intersectionality to understand migrant and refugee women’s experiences of gender-based violence during COVID-19

Abstract: Background Migrant and refugee women have faced a myriad of challenges during COVID-19, which are often exacerbated by the interaction between this population’s diverse identities and established systems in the local context. This qualitative study uses the lens of intersectionality to understand migrant and refugee women’s experiences of gender-based violence and access to and quality of support services in Italy during the first year of COVID-19. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 32 publications
0
12
0
1
Order By: Relevance
“…The Bangladeshi government, however, deemed sexual and GBV services as nonessential during COVID-19, impeding the ability of providers to continue service provision [67]. An Italian study showed that the COVID-19 pandemic converged with sexism, racism, and xenophobia, resulting in increased harassment and domestic violence against migrant and refugee women; provider and system constraints made access to remote sexual health services particularly difficult [9].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Bangladeshi government, however, deemed sexual and GBV services as nonessential during COVID-19, impeding the ability of providers to continue service provision [67]. An Italian study showed that the COVID-19 pandemic converged with sexism, racism, and xenophobia, resulting in increased harassment and domestic violence against migrant and refugee women; provider and system constraints made access to remote sexual health services particularly difficult [9].…”
Section: Resultsmentioning
confidence: 99%
“…Destination countries may attempt to limit migration flows through securitization, forced encampment and policies that criminalize attempted irregular border crossing. These strategies place migrant people, especially women and girls, at risk of violence, exploitation and forced labour and exacerbate existing health disparities [6][7][8][9]. Transit itself often increases health needs due to perilous physical conditions, erosion of social and financial support mechanisms, and limited access to basic health services [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…The data analysis procedures described here are part of a larger, mixed-methods research study that was conducted in four countries: Iraq, Italy, Guatemala, and Brazil. The aim of the larger study was to understand women and girls’ experiences of safety and well-being as well as their access to and availability and quality of GBV services [ 26 , 27 , 28 ]. The study also sought to understand service adaptations made by providers to promote continuity of service in the face of public health control measures.…”
Section: Methodsmentioning
confidence: 99%
“… 23 In Canada, an intersectional analysis of factors that affected access of minority immigrants to emergency/urgent care sought to understand migrant and refugee women’s experience of gender based violence during the pandemic. 26 27 A cohort study examining the intersectionality of obesity, chronic disease, social factors, and incident risk of covid-19 among low income, middle aged minority mothers in the United States showed who was being left out by current measures and was most at risk of covid-19. 28 Despite these examples, little primary research has been done that gives contextualised information about how pandemic measures affected health users and health workers.…”
Section: Research and Data Systems Must Prioritise Intersectionalitymentioning
confidence: 99%